The Assessment of Different Levels of Dental Participants on Designing a Removable Partial Denture (Mustansiria Dental Journal, 2019)
systematic approach to removable partial denture design is difficult and requiresthought planning. The correct design must be based upon accepted mechanical andbiological principles. This is an experimental study for drawing partial denture designfor selected cases on papers by different levels of participants and compares thesedesigns with a standard design taken mainly from a text book "McCracken'sRemovable partial prosthodontics". The results of this study shown that the highestpercentage of acceptable design for the total of three selected components ( majorconnector, rest and retainers) was 67.91% made by Prosthodontists followed by 49.16made by students, 29.58% made by general dental practitioners and finally the lowestpercentage was 23.33 that made by dental technicians .Also there are great variationsseen in different designs, some of them were far away from the principles ofremovable partial denture design, that lead to put in mind for more focusing onstudying removable partial denture design in dental schools.